2016
DOI: 10.3390/ijerph13101024
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Body Mass Index and Visual Impairment of School Students in Central China

Abstract: Body Mass Index (BMI) is a risk indicator for some eye diseases. However, the association between BMI and Visual Impairment (VI) was not quite certain in Chinese students. Our aim was to assess the relationship between BMI and VI with a cross-sectional study. A total of 3771 students aged 6–21 years, including 729 with VI, were sampled from 24 schools in Huangpi District of central China to participate in the study. A multistage stratified cluster random sampling was adopted. Each of the students answered a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…Although disease duration and HbA1C were not predictive of BCVA in type 2 diabetics with or without BRB leakage, baseline BMI was negatively correlated with BCVA at 12 and 24 months only in the group of type 2 diabetics with established BRB leakage, which is another subtle difference that we noted between the 2 groups. A previous study in Central China showed that overweight children are more likely to have visual impairment compared to normal weight children . Although that study agrees partially with our findings, we could not find any recent study in the literature that could explain why this relationship was only observed in type 2 diabetics with established BRB leakage.…”
Section: Discussionsupporting
confidence: 86%
“…Although disease duration and HbA1C were not predictive of BCVA in type 2 diabetics with or without BRB leakage, baseline BMI was negatively correlated with BCVA at 12 and 24 months only in the group of type 2 diabetics with established BRB leakage, which is another subtle difference that we noted between the 2 groups. A previous study in Central China showed that overweight children are more likely to have visual impairment compared to normal weight children . Although that study agrees partially with our findings, we could not find any recent study in the literature that could explain why this relationship was only observed in type 2 diabetics with established BRB leakage.…”
Section: Discussionsupporting
confidence: 86%
“…Findings from the present study support previous literature showing that obesity is negatively associated with ocular health including an increased risk of cataracts [7][8][9][10] and trouble seeing (eg, visual impairment [11][12] and poor visual acuity 13 ). For example, a US study including 87 682 women and 45 549 men followed for at least 10 years found that obesity was a risk factor for any type of cataract (relative risk = 1.36) after adjusting for several potential confounders (eg, age, smoking, and lutein/zeaxanthin intake), and that this association was the strongest for posterior subcapsular cataract.…”
Section: Interpretation Of the Findingssupporting
confidence: 90%
“…This increasing trend is of concern as obesity is an important risk factor for many chronic conditions such as cardiovascular disease, 2 diabetes, 3 cancer, 4 osteoarthritis, 5 and depression. 6 Importantly, in addition to the commonly recognized health outcomes associated with obesity, there is an increasing body of literature suggesting that overweight and obesity are associated with poor ocular health (eg, cataract, [7][8][9][10] visual impairment, 11,12 and poor visual acuity 13 ). For example, an Australian study of 3654 participants aged ≥49 years identified obesity as a risk factor for both cortical (odds ratio…”
Section: Introductionmentioning
confidence: 99%
“…Threshold effect analysis was conducted using Empower (R) (www.empowerstats.com, X & Y Solutions, Boston, MA). 24 P < 0.05 was the threshold for statistical significance. GraphPad Prism (6.01, San Diego, CA) and SPSS for Windows (13.0, Chicago, IL) were used for all statistical analyses and graphics.…”
Section: Discussionmentioning
confidence: 99%
“…Threshold effect analysis was conducted using Empower (R) (http://www.empowerstats.com, X & Y Solutions, Boston, MA) . P < 0.05 was the threshold for statistical significance.…”
Section: Methodsmentioning
confidence: 99%